2013
DOI: 10.1590/s0103-84782013005000033
|View full text |Cite
|
Sign up to set email alerts
|

Percepção e medidas de gestão de riscos por produtores de arroz irrigado na Fronteira Oeste do Rio Grande do Sul

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Climate-related events have been classified as very relevant for both rural production and other members of ASCs. They affect the quality of products, the quantities produced and production costs (Moreira, 2009;Ferreira Neto, 2012;Finger and Waquil, 2013). However, it is important to emphasize that, for the target of the present study, that is, slaughterhouses, climate events act more indirectly, given that they do not affect the development of the animals themselves, but the supply of food for them.…”
Section: Factor Analysis For the Socioenvironmental Constructmentioning
confidence: 94%
See 1 more Smart Citation
“…Climate-related events have been classified as very relevant for both rural production and other members of ASCs. They affect the quality of products, the quantities produced and production costs (Moreira, 2009;Ferreira Neto, 2012;Finger and Waquil, 2013). However, it is important to emphasize that, for the target of the present study, that is, slaughterhouses, climate events act more indirectly, given that they do not affect the development of the animals themselves, but the supply of food for them.…”
Section: Factor Analysis For the Socioenvironmental Constructmentioning
confidence: 94%
“…Factor 1, "Price risk," consisted of the variables "Oscillations in the prices of products," "Oscillations in the demand for products" and "Oscillations in the prices of raw material." Price oscillations are uncontrollable and are high-impact risk sources for both agriculture and agro industries (Vlajic et al, 2012;Finger and Waquil, 2013;Leat and Revoredo-Giha, 2013). In addition, the relationship between raw material prices and final product prices must be constant because increases in the cost of raw materials that are not passed on in the sale of products may make businesses unfeasible (Hallikas et al, 2002).…”
Section: Factor Analysis For the Market Risk Constructmentioning
confidence: 99%
“…These differences are addressed by Patrick et al (1985), Renn (1998) and Finger and Waquil (2013), who reported that the perception of risk differs considerably between groups of individuals and cultures.…”
Section: Perception Of Risk Sourcesmentioning
confidence: 99%
“…A number of studies in recent decades have assessed risk perceptions and risk management in agricultural and livestock activities (Flaten et al, 2005;Akcaoz et al, 2009;Borges and Machado, 2012;Finger and Waquil, 2013;Gebreegziabher and Tadesse, 2014;Khan et al, 2014). These studies are important because they show it is necessary to perceive risks to develop strategies to reduce or eliminate them.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this importance, several studies showed the academic interest in topics such as productivity, prices, costs, efficiency, and competitiveness of rice production, focused both in the South region and Brazil as a whole, as well as in other countries of the Southern Common Market (MERCOSUR) (ALVIM & WAQUIL, 2003;MARION FILHO & EINLOFT, 2008;CAPITANI et al, 2009;MARCHEZAN& SOUZA, 2010;HENKIN, 2010;IRETA-PAREDES et al, 2011;SOUZA & RÉVILLION, 2013;FINGER & WAQUIL, 2013).…”
Section: Introductionmentioning
confidence: 99%